Does childhood psychological maltreatment encourage you to become a cyberbullying perpetrator? The mediating role of negative affect and the moderating role of meaning in life - Zhang, Shujing; Li, Yi; Cao, Min; Liu, Yuxiao; Zhou, Zongkui (Frontiers in Psychology, 2023)
Objective: With the development of information and communication technology, cyberbullying among Chinese college students has become more frequent, bringing many negative consequences to both society and students themselves. Childhood psychological maltreatment may be one of the influencing factors of cyberbullying, but its internal mechanism remains poorly understood. This study aimed to explore the relationship between childhood psychological maltreatment and cyberbullying among college students and to further explore the mediating effect of negative emotion and the moderating effect of meaning in life.Methods: In this study, 656 college students (48.7% males) were recruited to complete anonymous questionnaires assessing their perceptions of child psychological maltreatment, negative affect, meaning in life and cyberbullying. SPSS23.0 and Hayes PROCESS macro for SPSS were used to conduct statistical analysis.(1) Childhood psychological maltreatment was significantly positively associated with cyberbullying; (2) Negative affect played a partially mediating role between childhood psychological maltreatment and cyberbullying; and (3) Meaning in life moderated the direct association between childhood psychological maltreatment and cyberbullying and moderated the association between negative affect and cyberbullying.In this study, a moderated mediation model was constructed and the internal mechanism of childhood psychological maltreatment and cyberbullying among college students was found. The results provided both theoretical contributions and practical suggestions for preventing cyberbullying.